Effect of whole-body vibration on postural stability in young adults with generalized joint hypermobility: A comparative study - Ewertowska, Paulina; Formella, Oskar; Poniatowski, Łukasz; Zielińska, Afrodyta; Krzysztofik, Michał; Czaprowski, Dariusz (Journal of back and musculoskeletal rehabilitation, 2024)
BACKGROUND: Whole-body vibration (WBV) is being used in rehabilitation and sport. Studies confirm its positive impact on muscle strength and power or regulating muscle hypertension. However, there are some uncertainties regarding its influence on postural stability. This issue seems particularly interesting in the case of individuals with generalized joint hypermobility (GJH), for whom proprioceptive training and muscle strengthening exercises are recommended while techniques that decrease muscle tension are not advised. OBJECTIVE: The aim of the study was to evaluate the acute effect of WBV on postural stability in adults with GJH. METHODS: 60 participants were categorized into the groups: 1) hypermobility with vibration (GJH+WBV), 2) hypermobility without vibration (GJH-WBV), 3) control group with vibration (CTRL+WBV), 4) control group without vibration (CTRL-WBV). The first and the third group completed WBV (frequency: 15 Hz and 30 Hz, amplitude 3 mm, 3 × 3 min). The second and fourth groups participated only in measurement sessions. GJH was assessed using the Beighton test. Postural stability was measured as the overall stability index (OSI) on the Biodex Balance System on the stable and unstable platform with open and closed eyes. Measurements were taken before and after WBV for two weeks. RESULTS: At a frequency of 15 Hz, a significant time effect was observed for measurements Before and After in CTRL-WBV on the stable platform with open eyes (p= 0.012) and on the unstable platform with closed eyes (p= 0.000) for the GJH+WBV and CTRL+WBV groups. There were no significant interactions (p> 0.05) between factors. At a frequency of 30 Hz, there was a significant time effect Before and After (p= 0.047) on the stable platform with open eyes, but no interaction was found between factors (p= 0.835). CONCLUSION: There is no positive acute effect of WBV on postural stability in adults with and without GJH.
Keywords: dospělí; mužské pohlaví; Young Adult; Adult; lidé; Joint Instability; Male; posturální rovnováha; vibrace; ženské pohlaví; Vibration; Postural Balance; Female; nestabilita kloubu; Humans; mladý dospělý